Effect of Forging Deformation and Cooling on Mechanical Properties of Martensitic Stainless Steel - Subagiyo; Syamsul Hadi; Sarjiyana; Bayu Pranoto (Logic : Jurnal Rancang Bangun dan Teknologi, 2021)
Stainless steel has good mechanical properties compared to other materials for strength and hardness, usually it will increase in hardness after hardening or forging. The purpose of this study was to obtain information about: The value of hardness and tensile strength of martensitic stainless steel forging with various deformations and cooling. The research method used is an experimental method, namely by forging on martensitic stainless steel with variations in deformation and cooling rate. Variations of forging deformation used are 25%, 50%, and 75%. The cooling media used are water, oil and air. The results of forgings with various cooling media were tested for tensile strength and tested for hardness using the Rockwell C (HRC) method. It was found that the higher the value of forging deformation, the higher the value of strength and hardness of martensitic stainless steel. This is because more and more martensite structures are recrystallized. In addition, it was also found that water and air cooling media gave an increase in the hardness of martensitic stainless steels. This is influenced by the cooling rate, where the higher the cooling rate, the more martensite structures formed, thus increasing the hardness value. The increase in hardness value is proportional to the increase in yield strength and tensile strength.